INNOVATIVE DEVELOPMENT OF NATIONAL ECONOMY – COMPETITIVENESS STATE IN INTERNATIONAL MARKETS - О. П. Радченко (Ринкова економіка: сучасна теорія і практика управління, 2016)
The analysis of features of national economy’s innovative development is conducted in the article. It is certain that Ukraine has its own model of innovative development. However cyclic character has indexes of innovative activity of national economy’s subjects that allowed drawing conclusion about imperfection of innovative development national model. Influence of innovations is shown on the competitiveness of the economic system that depends on introductions of new technique, technology, new management methods, new commodities and services, to new organization of management by a production, to new labor organization and her safety. It is educed, that over realization of the innovative programs brings to the competitiveness in international market. Strategy of the economic system’s innovative transformation is especially relevant for Ukraine. Combining the effects of globalized development with the increasing influence of technological factors have stimulated the modification of a modern economic model of the national economy development in which innovation becomes a key strategy to sustain competitiveness, growth and prosperity.